Analisis Kebutuhan Pasien Rawat Jalan Pada Pelayanan Kesehatan Primer: Studi Kasus Puskesmas Induk Kamaipura - Lexy Kareba; Sudirman Sudirman; Subardin AB; Parmi Parmi; Saiful Ambodale; Robert V. Pelima (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
According to Law Number 36 of 2009 concerning Health, Article 5, paragraph 2 states that everyone has an equal right to access resources in the health sector and obtain safe, quality, and affordable health services. Health services in Primary Health Care involve two parties, so Assessing the quality of service should involve both the perspective of the Primary health care and the patients. This study aims to measure the aspects most needed by the community in outpatient health services at Pprimary Health Care using service quality indicators. The study uses a quantitative descriptive approach with a factor analysis design. The study was conducted at the Kamaipura Main Primary Health Care, Sigi Regency, Central Sulawesi Province, in 2022. The variables in this study include tangibility, responsiveness, reliability, assurance, and empathy. Data collection was carried out through observations, with the population and sample consisting of all patients who used outpatient services at the Kamaipura Primary Health Care totaling 228 people. Outpatients have two levels of needs divided into two components. Variables are grouped into components based on the highest correlation. The first component consists of variables such as reliability, assurance, tangible, and responsiveness. Variables in the first component can be prioritized as follows: 1) Responsiveness, 2) Tangible, 3) Assurance, 4) Reliability. In conclusion All aspects of healthcare services, such as Reliability, Assurance, Tangible, Empathy, and Responsiveness, are primary needs for outpatient patients. The analysis indicates that Responsiveness, Tangible, Assurance, and Reliability need improvement.